Success of renewable energy projects under the financial and non‐financial performance measures. (1st July 2020) - Maqbool, Rashid; Deng, Xiaomei; Ashfaq, Saleha
Abstract: Around the globe, investment in renewable energy projects has been increased significantly since the last decade. However, recent trends of completed renewable energy projects are not positive enough regarding the significantly contributing through their operational performance. This study is an attempt to figure out the role of financial and non‐financial measures for the performance of renewable energy projects. A sample of 272x respondents was collected from the key project personnel in a view to assessing the influencing mechanisms of financial and non‐financial performance measures toward success in renewable energy projects. The data was collected through a convenient survey method from the employees working on managerial and technical positions in the small and medium‐sized renewable energy projects in Pakistan. Structural equation modeling (SEM) was used to perform data analysis and draw inferences. It was found that the success of renewable energy projects is largely depending on the influences of both financial and non‐financial performance measures. Moreover, both the financial and non‐financial performance measures were also found to be interlinked with each other positively and significantly. In addition, the role of financial performance measure compares to non‐financial performance measure was found to be more significant while contributing toward project success in renewable energy projects. The results also show that both the financial and non‐financial performance measures function as complements instead of substitute, while contributing toward renewable energy project success. Despite the role of financial measure is higher in contributing to project success as compare to non‐financial performance measure, ultimately both measures are necessary for sustainable project success in renewable energy projects. The research findings provide new insights for governments, policymakers, investors, and key stakeholders working on renewable energy projects to understand the measures driving better performance in such projects, alongside adding a knowledge base for future researchers and practitioners.